Energy Efficient Utilization toward Rural Biomass Waste by Straw Biogas Engineering - Xiao Wang; Dejie Zhao (Advances in Materials Science and Engineering)
In this article, we summarize and analyze the constraints and technical difficulties of biogas plants in clusters, storage and transportation yards, pretreatment yards, and anaerobic fields. Combined with Tyre’s own experience, several major techniques have been proposed. To guide and recommend the suitable technicians to decision makers, to acquire operation courses suitable for the general requirements of our biogas, and to promote the development of booth biogas seedlings in China, the use of environmental slam objects in a small and sufficient nonscale biogas program is formulated by the use of biogas funding alone. Current rating measures leverage the World Age Assessment (LCA) for the Integrated Booth Biogas Swing Type (typically 40,000 kWh) and Bio-Natural Gasoline Program (daily gasoline workload of 12,000 cubic curves). This is built upon the Environmental Impact Assessment and Analogy for Warships Both environmental stroke and sensitivity component analysis. These techniques include termination outlines, register analysis, dynamism drops for each performance stagecoach, and environmental issue calculations. According to the above summarization, when biogas dominates the family, the highest environmental emission becomes the biogas fermentation layer of the booth. Meanwhile, the most sympathetic substitute is the work cost of physical and chemical farting (mL g-1TS). The above two indicators denote the essence of biogas purification, and the choice of biogas purification technology. By evaluating the change in the impact of suppressing environmental emissions, the biogas substitute of scorpion charcoal has a remarkable improvement in the biogas equivalent of the charcoal-bright swing family. Comprehensive experimental results have demonstrated this conclusion.